An investigation into the role of attachment insecurities in obsessive-compulsive symptoms - Boysan, M.; Çam, Z. (Routledge, 2018)
The paper discusses the associations between adult attachment and OCD symptoms in light of current cognitive-behavioural theories of OCD. The role of attachment system in OCD has been increasingly recognised. The aim of this paper was to investigate and evidence for direct and indirect relations between attachment insecurities, obsessional beliefs and OCD symptoms. Data were collected from a sample of university students (N = 334) in a cross-sectional research design. Adjusting for age, sex, income, paternal education and maternal education, attachment anxiety and avoidance in combination with obsessional beliefs (responsibility/threat estimation, perfectionism/certainty and importance/control of thoughts) were regressed onto obssessionality using logistic regression analysis. One-way MANOVA comparisons of obsessionality and obsessive beliefs were run across four attachment styles. Finally, the affect regulation model of attachment theory was refined and tested in relation to OCD symptomatology. Attachment anxiety and attachment avoidance significantly contributed to severity of obsessive-compulsive symptoms. More specifically, respondents with fearful and preoccupied attachment styles reported greater scores on obsessive-compulsive symptomatology and obsessional beliefs. Using a structural modelling approach, we found responsibility/threat estimation significantly contributed to obsessional symptomatology via attachment anxiety and avoidance. © 2016, © 2016 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: adult attachment; affect regulation; interpersonal theory of OCD; Obsessive-compulsive disorder (OCD); prevention